Проблемная ситуация как средство обучения иностранному языку студентов лингвистического вуза - Белякова, Елена (Զանգակ հրատ.)
Հոդվածում վերհանվում են բարձրագույն ուսումնական հաստատություններում, մասնավորապես լեզվաբանական համալսարանում, լեզվի ուսուցման որոշ խնդիրներ: Հեղինակը կարևորում է տվյալ ֆակուլտետում ուսանողների լեզվի իմացության C1–C2 մակարդակների ապահովվումը, որի լուծումը նա տեսնում է դասապրոցեսում խնդրահարույց իրադրությունների ստեղծման և հաճախակի կիրառման մեջ: The article reveals some problems of language teaching in higher educational institutions, particularly in linguistic universities. The author points out the relevance of foreign language proficiency levels (C1–C2). After graduating the students should be linguistically, socially and culturally competent. The suggestion of the author is as follows: creating and developing problematic situations during the lessons will help students to become socially and professionally competent.
Keywords: Теория языка